Meat and milk quality and safety: past and future trends in Slovenia - Žgur, Silvester; Kovač, Milena; Golc Teger, Slavica; Holcman, Antonija; Donša, B.; Kompan, D. (Acta Agraria Kaposváriensis, 2006)
In Slovenia, meat production has stabilised in the last years. The important increase in meat production was noticed in sheep and goats. The quality of slaughtered cattle, estimated on the basis of noted conformation and fatness, has worsened in the last decade, mainly due to changes in the structure of cattle population. On the contrary, large improvement in quality was realized in pigs. Lean meat content increased around 6%. Sheep and goat meat production rapidly increased in the last 15 years (500%). Poultry meat producers have focused mainly to safe, healthy and functional products to satisfy the consumers’ needs. Milk production was limited by negotiated quotas and reached 635 million litres in the year 2005. Protein and fat content did not change in the last seven years, but the quality of milk regarding the number of total bacterial and somatic cell count greatly improved.